The kondo problem for very dilute ZnMn alloys under a Doorway State perturbation approach - Martín Landrove, Rafael (Ciencia, 1970)
An alternative perturbation treatment for the Kondo Problem is developed using a doorway state formalism for scattering process. Under this approach the behavior of resistivity is examined at the low temperature regime, below and above Kondo temperature, within the framework of the s-d model for very dilute ZnMn alloys, where the single impurity scattering assumption holds. The agreement with experiment is excellent in the entire low temperature regime.